The Beauty of Temis: An Aesthetic Explanation of Law (Mayéutica Revista Científica de Humanidades y Artes, 2022)
The aim of this essay is to reflect on Law from the perspective of art, that is, to make art out of Law. Legal aesthetics is a methodology of analysis that has an increasing number of adherents among jurists. However, the studies presented under this name are usually reduced to purely qualitative reflections (how art has graphed the Law) or pedagogical ones (how art allows us to understand the legal phenomenon), with the result that it can be observed that there is not a full understanding of what it means to make art out of the Law. Faced with this situation, in the following lines the reader will find a theoretical analysis of the legal from the point of view of aesthetics. In other words, an exercise in the theory of the art of Law.
Keywords: philosophy of Law; theory of Law; legal aesthetics; application of Law